Effects of adding nano-emulsified plant oil and probiotics to drinking water during different periods besides sex on processing characteristics, physicochemical properties, and meat quality traits of broiler chickens - Suliman, Gamaleldin M.; Hussein, Elsayed O. S.; Alsagan, Ahmed; Al-Owaimer, Abdullah N.; Alhotan, Rashed; Al-Baadani, Hani H.; Ba-Awadh, Hani A.; Qaid, Mohammed M.; Swelum, Ayman A. (Frontiers in Veterinary Science, 2023)
High-quality meat is one of the consumer demands. Therefore, several studies have concluded that supplementing broilers with natural additives can improve meat quality. This study was carried out to evaluate the effects of nano-emulsified plant oil (Magic oil®) and probiotic (Albovit®) as water additives (at the rate of 1 ml/L and 0.1 g/L, respectively) during different growing periods on processing characteristics, physicochemical properties, and meat quality traits of broilers chickens. A total of 432-day-old Ross broiler chicks were randomly assigned to one of six treatment groups according to the growing periods in which magic oil and probiotics were added to drinking water, each with nine replicates and eight birds per replicate (4♂ and 4♀). On day 35, birds’ processing characteristics, physicochemical properties, and meat quality traits were examined. The results showed that treatments had a significant (P  0.001) impact on cooking loss, cohesiveness, and chewiness. The male broiler chickens had higher (P ≤ 0.05) initial lightness, initial whiteness index, water holding capacity, shear force, live weight, hot and chilled carcass weights, as well as lower gizzard and neck percentages than females. The interactions between treatments and sex showed a significant (P  0.001) impact on cooking loss, shear force, hardness, springiness, and chewiness. In conclusion, supplementing male broiler chickens with Magic oil and probiotic, particularly from 0-30 days of age had good meat chewiness due to lower cohesiveness and hardness higher springiness, and the most convenient cooking loss value. Magic oil and probiotic, especially in males, is advisable to be supplemented in the water of growing broilers in chicken programs from 0 to 30 days of age. Moreover, further studies under commercial conditions are recommended to locate the most favorable combination of Magic oil/probiotic supplements for the best processing characteristics and meat quality attributes outcomes.